Novel Pliable Electrodes for Flexible Electrochemical Energy Storage Devices: Recent Progress and Challenges. Issue 17 (17th June 2016) - Yousaf, Muhammad; Shi, Hao Tian H.; Wang, Yunsong; Chen, Yijun; Ma, Zhimin; Cao, Anyuan; Naguib, Hani E.; Han, Ray P. S.
Abstract : With wearable electronics rapidly coming into fashion, research into flexible energy storage devices and in particular, pliable electrodes, is attracting a lot of attention. Pliable electrodes are usually fabricated by intercalating an active material in a flexible matrix with superior mechano‐electrical properties, and can be grouped either as substrate‐supported or free‐standing. Depending on their mode of deformation the electrodes can be labeled as bendable, compressible or stretchable. Recent progress and challenges in the design and fabrication of pliable electrodes for constructing flexible lithium ion batteries and flexible supercapacitors are highlighted. 2 pliable core‐shell structure electrodes fabricated from: a) carbon nanotube sponge embedded with MoS2 nanoparticles and b) electrospun polyethylene terephthalate fibers impregnated with graphene nanoplatelets are also presented. Abstract : Pliable electrodes are usually fabricated by intercalating an active material in a flexible matrix with superior mechano‐electrical properties. Their implementation in flexible lithium ion batteries and flexible supercapacitors still face many challenges. Two promising pliable electrodes are highlighted: carbon nanotube sponge embedded with MoS2 nanoparticles, and electrospun polyethylene terephthalate fibers impregnated with graphene nanoplatelets.